HUBUNGAN INDUKSI PERSALINAN DAN SEKSIO SESARIA DENGAN KEJADIAN ASFIKSIA PADA NEONATAL DI RUMAH SAKIT UMUM DAERAH KEPAHIANG TAHUN 2017 - Metha Fahriani (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
Section cesarean is performed on the factor of a high-risk pregnancy so that labor results in disruption to the fetus or newborn baby. The purpose of this study to determine the relationship of labor induction and section caesarea with the incidence of asphyxia on Neonatal in RSUD Kepahiang in 2017.This study used Case Control Study with population in this study were 610 baby with the amount of sample were 120 baby where 60 baby as case group and 60 baby as control group. Data analysis used chi-square. The results of this study showed: value of OR for labor induction were 2.44, means that babies born with labor induction had risk 2.44 times with incidence of neonatal asphyxia. For section caesarea showed: value of OR 2.64 means baby who labored with section caesarea had risk 2.64 times experiencing neonatal asphyxia. The results of this study showed that there was a significant relationship between induction of labor and section caesarea with the incidence of neonatal asphyxia in RSUD Kepahiang in 2017. Looked at the result of this study it is expected that the Hospital can improvement services in caring of baby ware and make an effort to prevent incidence of asphyxia through resuscitation to the baby, providing facilities and instrument to prevent incidence of asphyxia on baby with providing oxygen for the baby. Keywords: Asphyxia, labor induction, cesarean section